Pengaruh Shopping Lifestyle, Fashion Involvement, Dan Price Discount Terhadap Impulse Buying Pada Deliwafa Store Kota Malang (Studi Pada Mahasiswi Jurusan Administrasi Niaga Politeknik Negeri Malang) - Fitri Dwi Puspitasari; Baroroh Lestari; Eko Boedhi Santoso (PENG: Jurnal Ekonomi dan Manajemen, 2025)
The purpose of this study is to examine the impact of shopping lifestyle, fashion involvement, and price discounts partially  and simultaneously on impulse buying towards the Deliwafa Store. This study was a quantitative type using an explanatory research method that distributed questionnaires to 127 respondents. The sampling technique used was multistage sampling with cluster sampling, and purposive sampling. To analyze it, used descriptive techniques and multiple regression with hypothesis testing, classical assumptions, and analysis of the coefficient of determination. The results of the study showed that shopping lifestyle, fashion involvement, and price discounts have a partial and simultaneous impact on impulse buying. Several strategies are needed to increase impulse buying, namely by optimizing strategies to increase the attractiveness of the importance of family opinion in shopping lifestyle, strategies to increase consumer perceptions of fashion involvement, and strategies to increase the effectiveness of small discounts at price discounts.